Comparison of different treatment options in submacular haemorrhage - Anna Hillenmayer; Christian M. Wertheimer; Marlene Hillenmayer; Laura D. Strehle; Lennart M. Hartmann; Efstathios Vounotrypidis; Armin Wolf (BMC Ophthalmology)
Abstract Background/aims Submacular haemorrhages (SMH) cause significant visual impairment. Until now, the comparative effectiveness of different treatment approaches remains inconclusive without clear treatment guidelines. The aim of our study was to evaluate the effectiveness of 5 surgical treatment modalities in terms of visual prognosis and success rate. Methods This retrospective study included 201 patients with SMH. Primary endpoint was best corrected visual acuity (BCVA), secondary endpoints included haemorrhage size and complications. Group 1 was treated with pneumatic displacement and rtPA-injection. Group 2 followed the "Manchester protocol" with rtPA-injection and—if needed—a standardised secondary procedure with pars plana vitrectomy (ppV) and subretinal rtPA. Group 3 underwent vitrectomy with subretinal rtPA, group 4 vitrectomy only and group 5 received subretinal lavage. Results Baseline characteristics were a mean age of 79 years and a follow-up of 4.6 months. Pre-intervention BCVA of 1.7 logMAR improved to 1.4 logMAR at follow-up. A gain of > 0.2 logMAR was achieved in 47% of patients, while 20% lost > 0.2 logMAR. Only group 2 achieved a statistically significant visual gain. While group 5 was statistically larger in haemorrhage size preoperatively (p < 0.05), all groups were statistically equal in SMH size at follow-up. Complications led to additional interventions in 20% of patients. Conclusions No significant change in visual prognosis could be achieved depending on the intervention. As more invasive techniques seem to lack the benefit of a better postoperative prognosis while carrying higher risks, it may be beneficial considering a less invasive option first.